Pension Reform Primer : Issues, Challenges, Options and Arguments in Pension Reform - World Bank (Washington, DC, 2012)
The World Bank Pension Reform Primer aims to provide a comprehensive toolkit for policy makers on designing and implementing pension reform. It is based on continuously updated information from countries that have introduced reforms emphasizing the role of privately-managed individual retirement accounts. Their experience offers a number of useful lessons for policy makers elsewhere. The Bank set out a conceptual framework for fundamental pension reform in "Averting the Old Age Crisis: Policies to Protect the Old and Promote Growth". This study, published in 1994, helped shape the global debate about the impact of population ageing on pension systems. The Pension Reform Primer builds on this pioneering work and on the experience of the Bank, and other international institutions. It focuses on practical questions.